2008
DOI: 10.1122/1.2833469
|View full text |Cite
|
Sign up to set email alerts
|

Flows of concentrated suspensions through an asymmetric bifurcation

Abstract: Flows of concentrated suspensions at low Reynolds number through an asymmetric T-junction bifurcation composed of rectangular channels are studied experimentally using nuclear magnetic resonance imaging. In contrast to the unequal division of a uniform concentration material, the suspension and the neutrally buoyant, noncolloidal particles are almost equally partitioned between downstream branches, and motion of particles across the dividing stream surface is deduced to occur at the bifurcation. We attribute t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
27
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 41 publications
5
27
0
Order By: Relevance
“…To the best of our knowledge there are no experimental and simulation studies on flow of concentrated suspensions in symmetric three dimensional Y shape bifurcation channels that are common in microfluidic devices. In this work, we have studied In a previous study on migration in asymmetric T-junction bifurcation channel (Ahmed and Singh, 2011) the predictions from diffusive flux model were found to be in good agreement with the experiments of Xi and Shapley (2008). Thus, for simplicity of implementation, and economy of computations we have chosen diffusive flux model in our present study.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…To the best of our knowledge there are no experimental and simulation studies on flow of concentrated suspensions in symmetric three dimensional Y shape bifurcation channels that are common in microfluidic devices. In this work, we have studied In a previous study on migration in asymmetric T-junction bifurcation channel (Ahmed and Singh, 2011) the predictions from diffusive flux model were found to be in good agreement with the experiments of Xi and Shapley (2008). Thus, for simplicity of implementation, and economy of computations we have chosen diffusive flux model in our present study.…”
supporting
confidence: 82%
“…They observed that the particles are almost equally partitioned in downstream branches even though the flow partitioning is unequal. Later, Ahmed and Singh (2011) performed numerical simulations based on the diffusive flux model and obtained good agreement with the experimental work of Xi and Shapley (2008).…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…Interparticle interactions become dominant in concentrated suspensions, and, at low confinement, particles are almost equally divided between the downstream branches regardless of flow rate ratios [14].…”
mentioning
confidence: 99%
“…Volume excluded effects in the inlet channel, due to the existence of a zone near the channel wall unaccessible to the particles, and particle-wall hydrodynamic interactions are responsible for this different partitioning at bifurcations [16]. Several studies have addressed the role of particle deformability [17][18][19][20], concentration [21][22][23][24] and shape of bifurcation [16,24] on the fluid-particle partitioning. Finally, the enrichment/depletion of particles in the two outlet streams has been proposed as an effective mechanism to design simple microfluidic devices for particle separation [16], fractionation [16] and filtering [15].…”
mentioning
confidence: 99%